The Survival of a Temperate vtx Bacteriophage and an Anti‐Verocytotoxigenic Escherichia coli O157 Lytic Phage in Water and Soil Samples. (23rd June 2016) - Nyambe, S.; Burgess, C.; Whyte, P.; Bolton, D.
Summary: Verocytotoxigenic (vtx) Escherichia coli (VTEC) are zoonotic foodborne pathogens with the vtx operon encoded by lambdoid bacteriophage (phage). Despite much research on the host bacteria, similar data on the persistence of verocytotoxin converting phage and the ecological niches where transduction occurs are lacking and novel VTEC of important public health significance, have and continue to emerge. This study investigated the survival of a temperate vtx bacteriophage (24B ::kanamycin R ) in water (raw farm, pasteurized farm, laboratory tap and autoclaved purified water) and soil (sandy loam and loam soil). It also examined the persistence of an anti‐VTEC lytic phage (e11/2) in the same matrices as this may be one option for controlling the emergence of novel VTEC, especially in farm ecological niches where other control options, such as chemical, heat or high pressure treatments, are not feasible. Samples inoculated with 24B ::kanamycin R and e11/2 bacteriophage (8 log10 pfu/ml or pfu/g) separately were incubated at 4°C and 14°C, representative Irish Winter and Summer temperatures, respectively, and tested every 2 days for 40 days. The transduction of 24B ::kanamycin R was also continuously assessed. Both phages survived with reductions observed, regardless of matrix or storage temperature. Moreover, 24B ::kanamycin R was able to transduce its host E. coli strain. It was therefore concluded that aquatic and soil environments on farms may serve as a vtx phage reservoir and transduction point but anti‐VTEC phage is a possible biocontrol option.